The Relationship Between Religious Tribes In Tengger (Hindu, Islam and Budha) - M. Thoriqul Huda; Irma Khasanah (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
Indonesia including State that has a diversity of tribes, ethnicities, races, languages, religions, and cultures. However, with this diversity is able to cause conflict both internal and external. As with many cases going on in Indonesia. Religion is itself a foothold, beliefs, and guidelines for living, even too often scapegoats the incidence of conflict in society. However, the other by the tenggerese is located in Lumajang, Malang, Pasuruan Regency Probolinggo Regency here and there are three religions living side by side in one village i.e. Islam, Hinduism, and Buddhism. In the middle of kemajemukan different communities understand and belief turns out to be able to have an attitude of tolerance and mutual respect between each other. Keberanekaragaman religion is not an issue of community agrosari to interact in everyday activities.  Regarding religious tolerance have lately become a very good sticking issues among academics as well as the community. Local wisdom and culture be the solution to resolve the issue. Local wisdom on the tenggerese community of Javanese cultural values, as well as the cultural heritage of the Majapahit Empire which is still developing with mutual interlocking appreciate attitude, tolerance, and respect in the spirit of the ancestors and there is no tribal differences are striking in addition to differences of religious belief. The togetherness that is manifested in the form of the ritual customs such as the ceremony of the unan-unan, Bari'an (celebrate). Each religion has its own demands tolerance on the tenggerese is already deeply ingrained, tenggerese community also upholds the values of equality and democracy in the life of society as well as more respectful of religious leaders and shaman (spiritual teacher) than leader administrativ. Since all are brothers, all families, remain peaceful and trustful that became the pillars as well as ancestral heritage.